Loss of proteostasis is a pathomechanism in Cockayne syndrome - Alupei, Marius-Costel; Maity, Pallab; Esser, Philipp Ralf; Krikki, Ioanna; Tuorto, Francesca; Parlato, Rosanna; Penzo, Marianna; Schelling, Adrian; Laugel, Vincent; Montanaro, Lorenzo; Scharffetter-Kochanek, Karin; Iben, Sebastian (Cell reports, 2018)
Retarded growth and neurodegeneration are hallmarks of the premature aging disease Cockayne syndrome (CS). Cockayne syndrome proteins take part in the key step of ribosomal biogenesis, transcription of RNA polymerase I. Here, we identify a mechanism originating from a disturbed RNA polymerase I transcription that impacts translational fidelity of the ribosomes and consequently produces misfolded proteins. In cells from CS patients, the misfolded proteins are oxidized by the elevated reactive oxygen species (ROS) and provoke an unfolded protein response that represses RNA polymerase I transcription. This pathomechanism can be disrupted by the addition of pharmacological chaperones, suggesting a treatment strategy for CS. Additionally, this loss of proteostasis was not observed in mouse models of CS.
Gesehen am 11.05.2020